2010
DOI: 10.1007/s11270-010-0400-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Extraction Methods for the Assessment of Heavy Metal Bioavailability in Various Soils

Abstract: The main objective of this study was to compare the effectiveness of different methods (heavy metals in pore water (PW), diffusive gradients in thin films (DGT), diethylene triamine pentaacetic acid (DTPA) extraction, and total heavy metals (THM) in soil) for the assessment of heavy metal bioavailability from soils having various properties and heavy metal contents. The effect of soil heavy metal pollution on shoot yield and sulfatase enzyme activity was also studied. Wheat (Triticum aestivum) was grown in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 54 publications
6
27
0
1
Order By: Relevance
“…Our results are similar to those reported by Soriano-Disla et al [29] who reported good correlation between effective concentrations of Pb and its accumulation in plants. However, in highly contaminated soils, C E did not provide good predictions for the bioaccumulation of Pb.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are similar to those reported by Soriano-Disla et al [29] who reported good correlation between effective concentrations of Pb and its accumulation in plants. However, in highly contaminated soils, C E did not provide good predictions for the bioaccumulation of Pb.…”
Section: Resultssupporting
confidence: 93%
“…Using DIFS numerical model, the values of R diff calculated for soils from FE ranged between 0.0302 – 0.0316 and between 0.0219 – 0.0310 in BE. The effective concentrations ( C E ) of Pb in the unpolluted area ranged between 19.2 – 194 μg L −1 (average 37.3 μg L −1 ) in BE, being in the same order of magnitude with those reported by Soriano-Disla et al [29] for Pb in uncontaminated soils. In the polluted soil from FE, C E values ranged between 1050 – 7110 μg L −1 (average 3910 μg L −1 ), being about 100 times higher than in unpolluted area.…”
Section: Resultssupporting
confidence: 80%
“…Soil urease and phosphatase activities were often impacted by urea and organic material addition. This study showed that soil urease activities increased after urea was added and phosphatase activities were enhanced due to chicken manure addition, indicating their being environment-friendly (Soriano-Disla et al 2010). …”
Section: Resultsmentioning
confidence: 84%
“…Means within the same Cd treatments followed by the same letter (a-c) were not significantly different at p < 0.05 Means in the same Cd treatment columns followed by different letters were significantly different at p<0.05 EF enhancement factor, TF translocation factor the addition of fertilizer enhanced the soils nutritional indices without altering soil Cd concentration. The soil microorganism count and some enzyme activities reflect Cd as toxic to soil biology (Soriano-Disla et al 2010). Bacteria, fungi, and actinomycete counts were determined in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In previous decades, bioavailability of target elements in sediment has most often been measured by ex situ chemical methods, such as sequential extraction and single-step extraction methods (Menzies et al, 2007;Soriano-Disla et al, 2010). These equilibrium-based methods are based on operationally defined procedures, and they provide information on the concentrations of mobile or potentially mobile species in sediment that are available to biota.…”
Section: Introductionmentioning
confidence: 99%